From Valpuesta to Silos. The sources of castilian - Alvarez Tejedor, Antonio (Romanica Olomucensia, 2016)
From Valpuesta to Silos- The sources of Castilian is a scientific project that reflects the research, editorial and public outreach momentum driven by the Instituto Castellano y Leones de la Lengua and its efforts to determine, date and explain the first records of the Castilian Romance language. Furthermore, this document also represents an invitation to a real and imaginary trip to investigate the birthplaces of the Castilian language and its early written manifestations that can be found written in five different points of the Castilla Citerior or Castella Vetula. In this particular north-eastern region of Burgos we find the geographical, historical and cultural elements to date, define and explain the initial testimonies of the Castilian Romance language. It is the case of a language that appears here and there - in Valpuesta, Ona, Cardena, Covarrubias and Silos - in a sheltered easterly corner of Burgos, by the Cordillera Cantabrica, or in a hidden and remote valley of the West side of the Burgos side of the Sistema Iberico. This region and this society were not only the cradle for a new language but also for new legends, heroes, and myths that represent and lie at the core of Spanish and Hispanic culture: Los Siete Infantes de Lara, the Poema de Fernan Gonzalez, the Cantar de Mio Cid, etc. The Becerros Gotico y Galicano from Valpuesta, with documents dating between the ninth and thirteenth centuries, already show distinctive characteristics and features of the vocalism, morphology and syntax that are found in the Castilian Romance language. These Becerros de Valpuesta, together with other documentary collections from Burgos - Ona, 258 documents, Cardena, 373, and Covarrubias, 211 - have some of the oldest records to date of the spoken Romance language in Castile.
Keywords: Valpuesta; Ona; Cardena; Covarrubias; Silos; early Romance language; history of Spanish; cartularies; Becerro Gotico.